Entrepreneurial orientation, strategic flexibilities and indigenous firm innovation in transitional China. (14th January 2008) - Li, Yuan; Liu, Yi; Duan, Yi; Li, Mingfang
We build a systematic conceptual model to describe the relationship among entrepreneurial orientation, strategic flexibilities and the indigenous firm innovation, and empirically test how the entrepreneurial orientation affects the indigenous firm innovation through strategic flexibilities in the Chinese transitional economy. Our research findings provide a number of valuable insights.